2023
DOI: 10.1101/2023.01.15.524149
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hippocampal area CA2 controls seizure dynamics, interictal EEG abnormalities and social comorbidity in mouse models of temporal lobe epilepsy

Abstract: Temporal lobe epilepsy (TLE) is characterized by spontaneous recurrent seizures, abnormal activity between seizures, and impaired behavior. CA2 pyramidal neurons (PNs) are potentially important because inhibiting them with a chemogenetic approach reduces seizure frequency in a mouse model of TLE. However, whether seizures could be stopped by timing inhibition just as a seizure begins is unclear. Furthermore, whether inhibition would reduce the cortical and motor manifestations of seizures are not clear. Finall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…In epileptic mice, it has been reported that an increased occurrence of HFOs correlated to impaired memory 32 and that HFO disruption improves memory. 26 Thus, it is likely that the increased number of HFOs we found may affect memory performance at least in PS2KO and Ts65Dn mice that IIS appear to be infrequent. However, it is important to also consider that IIS alone have detrimental effects on memory.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In epileptic mice, it has been reported that an increased occurrence of HFOs correlated to impaired memory 32 and that HFO disruption improves memory. 26 Thus, it is likely that the increased number of HFOs we found may affect memory performance at least in PS2KO and Ts65Dn mice that IIS appear to be infrequent. However, it is important to also consider that IIS alone have detrimental effects on memory.…”
Section: Discussionmentioning
confidence: 84%
“…IIS and HFOs were detected using the same criteria as described in our previous studies. 12,13,16,26,27 We quantified IIS or HFOs that occurred during periods of wakefulness, SWS, or REM; these behavioral states were defined as before. 12,16 IIS were included if their amplitude exceeded the mean of the baseline noise by more than 5 standard deviations.…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary results indicate that both chemogenetic and optogenetic inhibition of CA2 pyramidal neurons reduce seizures in chronically epileptic mice [65]. According to a recent study, the contralateral hippocampus could be involved in seizure generation providing another potential target for LFS.…”
Section: Discussionmentioning
confidence: 94%
“…In future studies, it would be informative to apply LFS to CA2 neurons in the seizure focus since these cells survive SE well in ihKA mice [37] and MTLE patients [64]. Preliminary results indicate that both chemogenetic and optogenetic inhibition of CA2 pyramidal neurons reduce seizures in chronically epileptic mice [65]. According to a recent study, the contralateral hippocampus could be involved in seizure generation providing another potential target for LFS.…”
Section: Discussionmentioning
confidence: 99%
“…IIS were detected using the same criteria as described in our previous studies. 11,14,53 In brief, we included IIS that exceeded the mean baseline by more than 5 standard deviations (SDs) during the same behavioral state.…”
Section: Iis Detection and Iis Amplitude Analysismentioning
confidence: 99%